Surviving trees and deadwood moderate changes in soil fungal communities and associated functioning after natural forest disturbance and salvage logging. (March 2022) - Mayer, Mathias; Rosinger, Christoph; Gorfer, Markus; Berger, Harald; Deltedesco, Evi; Bässler, Claus; Müller, Jörg; Seifert, Linda; Rewald, Boris; Godbold, Douglas L.
Abstract: Temperate forests are increasingly subject to natural disturbance by stand replacing windthrows or bark-beetle attacks. Forests are commonly salvage logged after disturbance, whereby substantial parts of biological legacies, such as surviving trees and deadwood, are removed. Despite increasing concerns about the ecological consequences of salvage logging operations, our knowledge on the effects on the soil microbiome and associated functioning remains limited. Here, we studied soil fungal communities, decomposition processes, and soil organic matter dynamics in 21 intact or disturbed, temperate Norway spruce stands about one decade after they were damaged by windthrow or bark-beetle attacks. Disturbed stands comprised different post-disturbance management, i.e. deadwood retention and salvage logged plots. We used high-throughput sequencing and ergosterol measurements to explore fungal communities and biomass, and enzyme assays to study decomposition processes. Disturbance shifted soil fungal communities from ectomycorrhizal to saprotrophic dominated assemblages. Fungal biomass declined with decreasing tree abundance after disturbance. Activities of organic matter degrading enzymes declined by ca. 30–80% after disturbance. The relative abundance of ectomycorrhizal fungi was positively related to enzymatic activities. Tree biomass parameters and amounts of deadwood retained were positively related to fungal biomass, certain ectomycorrhizal taxa, and relative ectomycorrhizal fungal abundance among disturbed stands, which, in turn, was associated with higher enzymatic activities. Our findings demonstrate a significant response of soil fungal communities to natural forest disturbance and salvage logging, with consequences for decomposition and soil organic matter dynamics. We conclude that the retention of surviving trees and deadwood as biological legacies attenuated associated changes to a significant extent, highlighting their importance for the preservation of ectomycorrhizal fungi and the maintenance of decomposition processes after disturbance. Highlights: Natural disturbance and salvage logging reduced ectomycorrhizal fungal abundance. Fungal biomass decreased with decreasing tree abundance. Reduction in ectomycorrhizal fungi was associated with lower enzymatic activities. Surviving trees and deadwood buffered disturbance effects on soil fungi.